THE SETTING OF SCIENCE IN THE ELEMENTARY PROGRAM. - Parton, Daisy (Science Education, 1948)
The article focuses on the aims and objectives of the elementary school science program introduced in the U.S. schools. The science program aims to attain objectives of elementary education like helping children correctly to understand and interpret the world in which they live, helping them meet intelligently their problems of living, and helping them develop desirable social behavior and attitudes. An effective science program deals with the questions like how to provide a well-balanced science program and how to secure continuity of experience. They are questions which need much more study, thinking and experimentation on the part of those who are interested in the education of elementary school children. The objectives of the elementary school science program are the objectives of elementary education, and the content and the procedure in the science program stem from both society's needs and the nature and needs of children. A well rounded science program can provide opportunities for children to understand and meet more intelligently their problems in the various areas of living.